The Effect of Online Audio Visual Assisted Story Methods on the Listening Skills of Grade IV Students Elementary School: Pengaruh Metode Cerita Berbantuan Audio Visual secara Daring terhadap Keterampilan Menyimak Siswa Kelas IV SD - Dina Aufa; Supriyadi Supriyadi (Academia Open, 2022)
This study aims to determine the effect of the story method on listening skills of elementary school students. This research is motivated by the students' listening skills which are quite low in the classroom. This happens because the media is less attractive so that it makes students' listening skills lacking. This audio-visual- assisted storytelling method is used to have a positive impact on students' listening skills. This research was conducted at SDN Kalitengah 1 Sidoarjo. Researchers use quantitative research with the type of research Quasi Experimental Design. With the design form Noneequivalent Control Group. The effect of the audio- visual-assisted storytelling method on elementary students was analyzed using the t-test. The research subjects were 46 students, with 23 students in the control class and 23 students in the experimental class. The data were analyzed through 2 stages, namely pretest and posttest. Based on the results of the hypothesis test count with a significant level of a = 0.05 or 5%, it means 0.001 < 0.05 so that H0 is rejected and Ha is accepted. It can be concluded that there is an effect of the audio-visual-assisted storytelling method on the listening skills of elementary school students. From the eta squared analysis, it was obtained that 0.37 > 0.14 showed that the audio-visual-assisted storytelling method had a major effect on the listening skills of elementary school students.